Implikasi Hukum Klausula Baku Dalam Terms Of Service Tiktok Terhadap Upaya Perlindungan Hak Cipta - Silubun, Yosman Leonard; Sinaga, Jaya Setiawan (Universitas Jambi, Fakultas Hukum, 2024)
The presence of Tiktok leads to the growth of a new Content Creator that tries to create on the platform. To use the platform, a novice user is required to approve the Term of Service from the Tiktoks service provider. The term of service is a form of standard agreement that often contains standard clauses commonly used by application providers in the digital world. The purpose of this study is to find out the legal impact on the standard term of service clause of Tiktok on copyright protection efforts. The method used in this investigation is the method of normative law research. In principle, the use of standard clauses in terms of service is not prohibited by applicable laws in Indonesia. In Indonesian positive law, the use of a raw clause in a contract must meet the four valid conditions of the agreement under article 1320 BW and the default clause must not include an exemption from the liability of the entrepreneur as contained in article 18, paragraph 1 UUPK. The attempt to protect the copyright law is based on the fulfilment of the creator's exclusive right to the creation owned. The default term of service clause of Tiktok which lists the acquisition of copyrights without royalties, without exclusive rights, has been contrary to the prohibition of Article 82 Paragraph 2 UUHC. As a result of the law, the default Term of service Clause of the Tiktoke causes the agreement that has been agreed by the user of Tktok with the service provider to be annulled and cancelled by law because one of the clauses is contrary.